Analisis Hukum Pada Proses Penyelesaian Konflik Dalam Pelaksanakan Pernikahan Dengan Tradisi Ontalan - Muhamad Musta’in (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This research was conducted to gain a different perspective on the ontalan tradition, which is the practice of giving severance pay to newlyweds as a form of charity that is carried out openly and aims to strengthen ties within the community. This tradition is not required by Islamic law, but is respected as a custom that reflects the solidarity and concern of the community. The research was conducted using a normative legal method, employing secondary data sources obtained from a review of relevant literature related to the issue under discussion. The findings of this study reveal how the local community views the ontalan tradition as an expression of care and generosity towards the bride and groom, aligning with Islamic teachings on the importance of charity and assisting others.